Pengaruh Direct Instruction Dan SQ3R Terhadap Retensi Siswa Dalam Pembelajaran Biologi: (The Effects of Direct Instruction and SQ3R on Student Retention In Biology Learning) - Agustianda, Selpiana; Meilinda, Meilinda; Nazip, Khoiron; Genisa, Marlina Ummas; Sumah, Astrid SW; Ismail, Gunawan (BIODIK, 2024)
The coordination system is one of the biology materials that students find difficult to remember (retention) let alone understand the concept because many have scientific terms. This study aims to determine the effect of student retention on biology learning on nervous system material through the application of Direct Instruction (DI) and Survey, Question, Read, Recite, Review (SQ3R). The method used is a Quasi-Experimental Design category Posttest Group Design. Data was collected through 2 stages of testing. The first stage is short-term retention in the form of final test 1 taken after the learning process, then the second stage (long-term retention) through the 2nd final test is taken 3 weeks after final test 1. The results show that the percentage of long-term retention short students use DI of 62.5% and SQ3R of 78.125%, which means that both are categorized very well. The same is true for the category of students' long-term retention percentage when using DI of 56.25% and SQ3R of 68.75% which are also classified as very good categories. The use of DI and SQ3R in biology learning can be said to have a positive effect, but student retention is more enhanced through SQ3R learning than the application of DI. Abstrak. Sistem koordinasi merupakan salah satu materi biologi yang dianggap sulit oleh siswa untuk diingat (retensi) apalagi memahami konsepnya karena banyak memiliki istilah ilmiah. Penelitian ini bertujuan untuk mengetahui pengaruh retensi siswa terhadap pembelajaran biologi pada materi sistem koordinasi melalui penerapan Direct Instruction (DI) dan Survey, Question, Read, Recite, Review (SQ3R). Metode yang digunakan adalah Quasi Experimental Design kategori Postest Group Design. Data dikumpulkan melalui 2 tahapan tes. Tahap pertama merupakan retensi jangka pendek berupa tes akhir 1 diambil setelah proses pembelajaran, kemudian tahap kedua (retensi jangka panjang) melalui tes akhir ke 2 diambil 3 minggu setelah tes akhir 1. Hasil menunjukkan bahwa persentase retensi jangka pendek siswa menggunakan DI sebesar 62,5% dan SQ3R sebesar 78,125% yang artinya keduanya terkategori sangat baik. Hal yang sama pada kategori persentase retensi jangka panjang siswa saat menggunakan DI sebesar 56,25% dan SQ3R sebesar 68,75% yang juga tergolong kategori sangat baik. Penggunaan DI dan SQ3R dalam pembelajaran biologi dapat dikatakan memiliki efek positif, namun retensi siswa lebih ditingkatkan melalui pembelajaran SQ3R daripada penerapan DI.